Tunneling nanotubes provide a new route for bovine viral diarrhea virus spreading - Yin, Jiying; Zhou, Zehui; He, Ning; Zhou, Hongming; Liu, Xiaoqun; Zhao, Yixing; Zhao, Longge; Zhang, Jiating; Zhu, Yanan; Zong, Ying; Diao, Naichao; Shi, Kun; et al. (Frontiers in Veterinary Science, 2025)
IntroductionBovine viral diarrhea virus (BVDV) is one of the major pathogens currently endangering the world's cattle industry. It poses serious difficulties in prevention and treatment because it can infect cattle of all ages and the specific mechanism of its cell-to-cell transmission has not yet been fully clarified. Tunneling nanotubes (TNTs) are F-actin-rich tubules that connect to the cytoplasm of nearby cells. They have been found to play an important role in the transmission of several viruses, but studies on BVDV in TNTs have not been reported.MethodsFirstly, the transwell assay was employed to investigate the transmission routes of BVDV and its capacity to propagate via intercellular junctional structures in the presence of neutralizing antibodies. Secondly, preliminary characterization of these junctional structures was conducted through pharmacological intervention experiments using the microtubule stabilizer paclitaxel, the microtubule disruptor nocodazole, the F-actin disruptors cyclosporine D and spongiosin A, and the gap junction blocker glycine. Subsequently, we validated the composition, spatial positioning, microscopic morphology, and generation characteristics of intercellular junctional structures following BVDV infection. Finally, iSTORM and live-cell fluorescence dynamic imaging techniques, we observed the transmission of BVDV viral particles through TNTs.ResultsTranswell assays demonstrated that BVDV can be transmitted via direct intercellular contact, a mode of transmission unaffected by neutralizing antibodies. Pharmacological studies revealed that only the F-actin disruptors spongin A and cell relaxin D inhibited the formation of this structure, preliminarily identifying it as a tunnel nanotube. Validation experiments confirmed that the composition, spatial orientation, microstructure, and formation direction of this connecting structure align with tunneling nanotube characteristics, further substantiating its identity as TNTs. iSTORM and live-cell fluorescence dynamic imaging revealed that BVDV particles can traverse TNTs to complete intercellular infection.DiscussionWe first report that BVDV can induce the formation of tunneling nanotubes and exploits this route to spread to uninfected cells. Our data highlight a previously unknown route of BVDV spreading, which could have significant implications for celler transmission and immune evasion.